Language ability of young English language learners: Definition, configuration, and implications. (January 2015) - Gu, Lin
In this study I examined the dimensionality of the latent ability underlying language use that is needed to fulfill the demands young learners face in English-medium instructional environments, where English is used as the means of instruction for teaching subject matters. Previous research on English language use by school-age children provided evidence that language proficiency for academic studies relates to, yet differs from, the language ability needed for social communications. Focusing on learners of English as a foreign language (EFL), I investigated the nature of language proficiency of school-age EFL learners in light of their learning experience. Analyses were based on test performance from the TOEFL Junior® Comprehensive test a proficiency assessment of English as a foreign language for young learners between the ages of 11 and 15, developed by the Educational Testing Service. The results showed that the two ability constructs (i.e., academic and social language), although theoretically distinct and educationally relevant, were statistically indistinguishable based on EFL learners' test performance. It was also found that the test performance could be explained best by a higher-order model, indicating that the language ability of these young EFL learners was structurally similar to that usually found with adult learners in a foreign language environment. The outcomes highlight the interrelatedness of learning environment, age and language proficiency. On the one hand, the nature of the ability construct can vary across groups of learners due to differences in learning environments. On the other hand, learners of different ages who share similar learning environments could be similar in terms of the latent representation of their language proficiency. The study concludes that the interpretation of young EFL learners' language proficiency needs to take into consideration how language components are developmentally related to each other as a function of learning experience in a foreign language environment.